Integration Guidance and Strategic Alignment Proposal - Altshul, Helen J. (CGIAR System Organization, 2025)
This report provides practical guidance for embedding responsible innovation and scaling within the CGIAR’s frameworks and tools. It introduces relevant external frameworks (IDRC, RRI, WUR, OECD, GIZ, CSIRO, GRP, TIP) and presents actionable prompts, tag-in menus, and entry points designed to help teams integrate reflection on inclusion, legitimacy, and learning into everyday processes.